cDrake CPIES Data Report November 2007 to December 2011 - Tracey, Karen L.; Donohue, Kathleen; Watts, D. Randolph; Chereskin, Teresa (DigitalCommons@URI, 2013)
The goal of cDrake is to quantify the transport and understand the dynamic balances of the Antarctic Circumpolar Current (ACC) in Drake Passage. For this purpose, a transport line spanning all of Drake Passage and a local dynamics array of CPIES were deployed for a period of four years. A CPIES comprises an inverted echo sounder equipped with a bottom pressure gauge and a current meter tethered 50 m above the bottom. In addition to the CPIESs, three current meter moorings were deployed along the continental margins for the initial two years of the field program. Subsequently, a current meter comparison mooring was deployed in a region of strong bottom currents for a period of one year. Conductivity-temperature-depth and lowered acoustic Doppler current profiler measurements were taken at each CPIES site. Shipboard acoustic Doppler current profiler measured the velocity structure along the cruise track. In this report, the CPIES data collected during the field experiment are presented. The collection, processing and calibration of the CPIES are described.